2020
DOI: 10.29121/ijetmr.v6.i10.2019.457
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Mentoring Programs at Academic Institutions: A Systematic Literature Review and Suggestions for Future Mentoring Programs

Abstract: Teaching is the oldest profession in the world. Mentoring program for faculty only began as recently as the 1970’s. While there are many types of mentoring programs, there is a clear need for more mentoring programs as the demographics of faculty have changed. Single parent faculty, women, minorities and foreign faculty need mentoring programs. Research has shown that there is a clear link between mentoring programs and retention of faculty. Furthermore, mentoring programs are needed at academic institutions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Unfortunately, faculty advisors generally do not receive formal mentor training. Instead, they often learn mentoring skills informally from peer observations or by trial and error [16][17][18][19], even though prior studies have shown that faculty could greatly benefit from formal training programs by developing and improving their mentor skills [16,19,20]. This paper presents and promotes an innovative mentor training program, the Advancement of Mentoring Practice Program (AMPP).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, faculty advisors generally do not receive formal mentor training. Instead, they often learn mentoring skills informally from peer observations or by trial and error [16][17][18][19], even though prior studies have shown that faculty could greatly benefit from formal training programs by developing and improving their mentor skills [16,19,20]. This paper presents and promotes an innovative mentor training program, the Advancement of Mentoring Practice Program (AMPP).…”
Section: Introductionmentioning
confidence: 99%